Habeas corpus no Brasil: restrições à garantia fundamental pelo Supremo Tribunal Federal - JOÃO MATHEUS FRANCO GIACOMINI (2021)
Habeas corpus, a constitutional right declared by the Federal Constitution and International Treaties, has been subject to limitations set by the jurisprudence of the Brazilian Supreme Court. The purpose of this paper is to demonstrate the present restrictions to admissibility and processing of habeas corpus in the Federal Supreme Court due to recent legal precedents. To do so, its objectives are to analyze the writ historically, since its birth on English soil and its context in the United States; to also evidence its birth in the Brazilian legal system, within its historical and social contexts; and to demonstrate its constitutional status from 1891 until now. Adopting the post-positivist paradigm, the research approach is historical and dogmatic, as the legal system and its values are analyzed, as well as its social and cultural contexts. Regarding its means, bibliographical and documentary research is conducted based on books, legal journals and papers, legislation, and jurisprudence. Since there is need for in-depth study of the topic, exploratory research is employed; finally, research is descriptive and explanatory, as it outlines its objects, as well as critically analyzes the precedents set by the Supreme Court on the matter, as well as the practical consequences regarding nature and speed of habeas corpus. Changes in the function of habeas corpus throughout time, depending on social and judicial context, have been observed, in the English, American and Brazilian law. Also, an exemplary list of habeas corpus restrictions by the Brazilian Supreme Court has been noticed: the limitation originated from the legal precedent n. 691 of the Supreme Court, which impedes the motion which intends to overrule the denial of a habeas corpus in a preliminary injunction; outline the need to exhaust higher court motions using interlocutory and special appeals according to high court regulations; the limitation to the writ of habeas corpus used, in the First Panel, in replacement of ordinary and extraordinary appeals, as well as interlocutory appeals and judicial reviews, due to a precedent set by Supreme Court Justice Marco Aurélio in 2012; the imposition, by the First Panel, of a new habeas corpus writ to the Supreme Court upon a definitive ruling by inferior courts; the obstacle to the usage of the habeas corpus against singular decisions of a Justice or Panels of the Supreme Court, according to the legal precedent n. 606; and the limitations to habeas corpus decisions issued by force of law [ex officio].